Cementing the Organic Farming by Green Manures - Bista, Bishal; Dahal, Sagar (International Journal of Applied Sciences and Biotechnology, 2018)
In this modern era of chemicals, the haphazard use of chemical fertilizers, pesticides, insecticides and weedicide is becoming a great concern. Accumulation and magnification of those toxic materials in soil is degrading soil health and also affects the human health indirectly. Hence, Agriculture is concentrating more towards organic, sustainable and eco-friendly measures of production. Provision of healthy organic products is a great challenge for modern agriculturist (Farmers). Organic farming relies on judicious use of FYM, Compost, Vermicompost, Green manures and several other factors. Green manures are organic sources for amelioration of soil physical, chemical and biological properties. Furthermore, Green manure conserves the soil available nutrients and suppresses the losses incurred due to erosion, leaching etc. Not only that, Green manure inhibits the several disease, pests and weeds. Int. J. Appl. Sci. Biotechnol. Vol 6(2): 87-96